The relationship between lower urinary tract symptoms and health status: the UREPIK study. - Boyle, P; Robertson, C; Mazzetta, C; Keech, M; Hobbs, R; Fourcade, R; Kiemeney, L; Lee, C (2003)
OBJECTIVES: To assess the hypothesis that as lower urinary tract symptoms (LUTS) increase in severity, the impact as measured by the BPH impact index (BII) would also increase. SUBJECTS AND METHODS: The UREPIK survey collected information on this relationship from men and their partners in the Netherlands, Korea, France and the UK. Culturally and linguistically validated versions of three standard questionnaires, the SF-12, the BII and the International Prostate Symptom Score (IPSS) were used to assess the distribution of symptoms and the impact on health status. Stratified random samples of men aged 40-79 years in each community were recruited. Response rates were 72% in Boxmeer, 28% in Auxerre, 60% in Birmingham and 68% in Seoul. Regression analyses were undertaken on total SF-12, BII and IPSS. RESULTS: In all, 4800 index men and 3674 women responded; the BII increased with increasing IPSS. The correlation coefficients were; Boxmeer 0.69, Auxerre 0.56, Birmingham 0.60 and Seoul 0.68. For women, the correlations were slightly lower except in Birmingham, at 0.65 (Boxmeer), 0.44 (Auxerre), 0.71 (Birmingham), 0.57 (Korea). BII scores were higher in women than in men with the same level of IPSS. Adjusting for IPSS there was no association between age and BII. There was an association between IPSS quality-of-life (QoL) score and BII; for men the correlation was 0.62 and for women 0.60. Men and women with the same score on the IPSS QoL reported the same bother. Among those with an IPSS of 20-35 women expressed significantly more bother (P < 0.001). The SF-12 scores decreased as the IPSS and the BII increased in both men and women. Furthermore, the SF-12 mental score decreased with increasing symptoms in the partner. CONCLUSIONS: The relationship between the severity of LUTS and BII was similar in all centres. There is a clear association between the BII and the IPSS QoL question in men and women. The BII discriminates between people who are unhappy about their urinary condition compared with those who are pleased. Although designed for use in men with benign prostatic hyperplasia, the index also appears to be a useful among women. The severity of symptoms of LUTS has an adverse effect on the health status of the individual and his/her partner.